Human resources for health in Botswana: The results of in-country database and reports analysis - Oathokwa Nkomazana; Wim Peersman; Merlin Willcox; Robert Mash; Nthabiseng Phaladze (AOSIS, 2014)
Background: Botswana is a large middle-income country in Southern Africa with a population of just over two million. Shortage of human resources for health is blamed for the inability to provide high quality accessible health services. There is however a lack of integrated, comprehensive and readily-accessible data on the health workforce. Aim: The aim of this study was to analyse the existing databases on health workforce in Botswana in order to quantify the human resources for health. Method: The Department of Policy, Planning, Monitoring and Evaluation at the Ministry of Health, Ministry of Education and Skills Development, the Botswana Health Professions Council, the Nursing and Midwifery Council of Botswana and the in-country World Health Organization offie provided raw data on human resources for health in Botswana. Results: The densities of doctors and nurses per 10 000 population were four and 42,respectively; three and 26 for rural districts; and nine and 77 for urban districts. The average vacancy rate in 2007 and 2008 was 5% and 13% in primary and hospital care, respectively, but this is projected to increase to 53% and 43%, respectively, in 2016. Only 21% of the doctors registered with the Botswana Health Professions Council were from Botswana, the rest being mainly from other African countries. Botswana trained 77% of its health workforce locally. Conclusion: Although the density of health workers is relatively high compared to the region, they are concentrated in urban areas, insuffiient to meet the projected requirements and reliant on migrant professionals.